Orders by the Minister of Health of the Republic of Lithuania - State Health Care Accreditation Agency under the Ministry of Health of the Republic of Lithuania infmors (Slauga. Mokslas ir praktika, 2020)
Valstybinės akreditavimo sveikatos priežiūros veiklai tarnybos prie SAM informacija.